Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A remotely triggered phase change hydrogel dressing for controlled release and promoting healing of infected wounds - Xiaolong Hu; Hongyan Zhang; Zuan-Tao Lin; Yu Chen; Hao Cheng; Bi-Huan Zhong; Yongli Li; Xiao-Ping Liao; Jian Sun; Mei X. Wu; Gang-Biao Jiang (Chemical Engineering Journal, 2025)

Metabolic mechanism, responses, and functions of genes HDH1, HDH3, and GST1 of tea (Camellia sinensis L.) to the insecticide thiamethoxam - Ping Zhang; Tianyuan Yang; Yunlong Xie; Yulong Liu; Qing X. Li; Xiangwei Wu; Rimao Hua; Weiting Jiao (Journal of Hazardous Materials, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Fertilization and tillage influence on soil organic carbon fractions: A global meta-analysis - Chun Liu; Chunhuan He; Scott X. Chang; Xinli Chen; Shaoshan An; Dong Wang; Jing Yan; Yuheng Zhang; Ping Li (CATENA, 2024)

Evaluating drought monitoring utility of the top-down and bottom-up satellite precipitation products over mainland China from a three-dimensional perspective - Yuefen Zhang; Chuanhao Wu; Pat J.-F. Yeh; Jianzhu Li; Jiayun Li; Bill X. Hu; Ping Feng (Journal of Hydrology, 2023)

Pyrrolizidine-producing weeds in tea gardens as an indicator of alkaloids in tea - Weiting Jiao; Luyao Wang; Lei Zhu; Tingting Shen; Taozhong Shi; Ping Zhang; Chen Wang; Hongping Chen; Xiangwei Wu; Tianyuan Yang; Qing X. Li; Rimao Hua (Food Additives & Contaminants Part B-Surveillance, 2023)

Impacts of climate anomalies on the interannual and interdecadal variability of autumn and winter haze in North China: A review - Jing Wang; Yanju Liu; Yihui Ding; Ping Wu; Zhiwei Zhu; Ying Xu; Qiaoping Li; Yingxian Zhang; Jinhai He; Julian X. L. Wang; Li Qi (International Journal of Climatology, 2020)
From the perspectives of remote sensing and climatic factors like surface meteorological parameters, large‐scale atmospheric circulations, and external forcing factors (EFFs), the authors synthesize and review spatiotemporal variations of PM 2.5 over North China and how climate anomalies affect autumn and winter haze variability in North China according to recent studies. This review focuses on both interannual and interdecadal timescales. It is shown that circulations play an important role in influencing haze variability. Atmospheric circulations, which would be modulated by EFFs like sea surface temperature, sea ice, and snowpack, can affect the climate variability in haze over North China via modulation of surface‐layer parameters that are closely connected with the haze phenomenon. Therefore, EFFs are deemed significant factors impacting the climate variability of haze over North China, serving as paramount precursory signals for haze prediction. Furthermore, this paper suggests potential future research directions for haze variability studies in North China on the basis of summarizing and concluding the associated processes/mechanisms on how climatic factors affect haze variability, which could provide reference for treating and forecasting in situ hazy conditions.

Morphogenesis and Gene Mapping of deformed interior floral organ 1 (difo1), a Novel Mutant Associated with Floral Organ Development in Rice - Lianping P. Sun; Yingxin X. Zhang; Peipei P. Zhang; Zhengfu F. Yang; Xiaoxiao X. Zhou; Dandan D. Xuan; Md Habibur H. Rahman; Zihe H. Li; Weixun X. Wu; Xiaodeng D. Zhan; Xihong H. Shen; Ping Yu; et al. (Plant Molecular Biology Reporter, 2017)

Bioaccumulation and Elimination of the Herbicide Clomazone in the Earthworms Eisenia fetida - Jia Cao; Ping Li; Qing X. Li; Pengfei Zheng; Xiaoping Diao (Bulletin of Environmental Contamination and Toxicology, 2015)

Neurology of the H1N1 pandemic in Singapore: a nationwide case series of children and adults - Asha Prerna; Jocelyn Y. X. Lim; Natalie W. H. Tan; Mas Suhaila Isa; Helen May-Lin Oh; Norazieda Yassin; Chian-Yong Low; Derrick W. S. Chan; Chia-Yin Chong; Yee-Sin Leo; Angela Li-Ping Chow; Paul Ananth Tambyah; et al. (Journal of NeuroVirology, 2015)

Catalytic ozonation of petroleum refinery wastewater utilizing Mn-Fe-Cu/Al2O3 catalyst - Chunmao Chen; Brandon A. Yoza; Yandan Wang; Ping Wang; Qing X. Li; Shaohui Guo; Guangxu Yan (Environmental Science and Pollution Research, 2015)

Bimodal voltage dependence of TRPA1: mutations of a key pore helix residue reveal strong intrinsic voltage-dependent inactivation - Xia Wan; Yungang Lu; Xueqin Chen; Jian Xiong; Yuanda Zhou; Ping Li; Bingqing Xia; Min Li; Michael X. Zhu; Zhaobing Gao (Pflügers Archiv - European Journal of Physiology, 2014)

Water quality of a tributary of the Pearl River, the Beijiang, Southern China: implications from multivariate statistical analyses - Ming W. Song; Ping Huang; Feng Li; Hui Zhang; Kai Z. Xie; Xi H. Wang; Guo X. He (Environmental Monitoring and Assessment, 2011)

New insights into the role of angiotensin-converting enzyme obtained from the analysis of genetically modified mice - Xiao Z. Shen; Hong D. Xiao; Ping Li; Chentao X. Lin; Sandrine Billet; Derick Okwan-Duodu; Jon W. Adams; Ellen A. Bernstein; Yi Xu; Sebastien Fuchs; Kenneth E. Bernstein (Journal of Molecular Medicine, 2008)

Molecular cloning and characterisation of a non-TIR-NBS-LRR type disease resistance gene analogue from sugarcane - Q. You-Xiong; L. Jian-Wei; Z. Ji-Sen; R. Miao-Hong; X. Li-Ping; Z. Mu-Qing (Sugar Tech, 2008)

Short timescale air-sea coupling in the tropical deep convective regime - S. Gao; F. Ping; X. Cui; X. Li (Meteorology and Atmospheric Physics, 2006)

An ultra-metastatic model of human colon cancer in nude mice - Fang X. Sun; Aaron R. Sasson; Ping Jiang; Zili An; Reza Gamagami; Lingna Li; A.R. Moossa; Robert M. Hoffman (Clinical & Experimental Metastasis, 1999)